2. Antecollis associated with Parkinson's disease improved following apomorphine therapy. Issue 3 (March 2016) - Yin, Y.W.K.; Chang, F.C.F.; Mahant, N.; Fung, V.S.C.; Tsui, D.; Aldaajani, Z.; Adam, R.; Hely, M.
Abstract : Antecollis is dystonia of the neck resulting in excessive forward flexion, often associated with dysphagia. It is generally associated with the later stages of Parkinson's disease (PD) and is often refractory to medical and botulinum toxin therapy. We report improvement in antecollis in a PD patient following subcutaneous apomorphine therapy. We report a 70 year old lady with idiopathic PD diagnosed 12 years ago. She presented with unilateral levodopa responsive hand tremor with akinesia and rigidity. 12 months ago, during treatment with levodopa 600 mg daily and pramipexole ER 3 mg daily, she developed acute antecollis over 24 h after a fall with minor head injury. Reduction in pramipexole to 2.25 mg daily made no difference. Over 8 months she developed gradual worsening of antecollis with reduced oral intake, weight loss and reduce mobility. She had visual hallucinations with insight. On examination she had normal neck extensor strength. There was no rigidity and minimal bradykinesia in the extremities. Administration of oral medication via nasogastric tube was ineffective. An apomorphine challenge was performed after pre-treatment with domperidone. There was acute improvement in hand function, rigidity and mobility without speech or neck posture improvement. However, neck posture started to improve 4 h post apomorphine administration. Apomorphine was commenced regularly at 2 mg subcutaneous injections 3 times a day. This was well tolerated with mild generalized dyskinesia and no hallucinations. At 2 and 4 months followup, the patient had significant improvement in swallowing and resolution of antecollis. She was able to feed, transfer herself and play the piano again and gained 8 kilograms. She had presence hallucinations at night with retained insight. At 7 months followup she had recurrence of antecollis and dysphagia which improved following cessation of pramipexole and commencement of an apomorphine 16 h daytime infusion with nocturnal rotigotine patch therapy. Apomorphine therapy may be an useful treatment for antecollis in PD.